Draf laporan pendekatan kajian rancangan tempatan daerah Kuala Pilah, Negeri Sembilan 2035 (penggantian) - Zainal, Megat Shahir; Razak, Mohd Zainal; Asmawi, M. Zainora; Zainal Abidin, Azean; Abidin, Suriani; Mohammad Nazri, Fathin Nahdrah; Nik Rashid, Nik Husni; Zainal, Megat Shahir; Yahya, Mohd Zaki; Muhammad Adilah, Nurul Anis Shazreena; Azman, Muhamad Amirul; Mohamad Zainudin, Mariani; et al. (PLANMalaysia@Negeri Sembilan, 2019)
The report of approach addresses the overall and sectoral methodologies to conduct the study of a local plan for the district of Kuala Pilah, Negeri Sembilan. It also covers the preliminary issues related to the site which to be verified in the stage of analyisis.